2013
DOI: 10.1016/j.pmn.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Adolescent, Caregiver, and Clinician Perceptions of the Impact of Migraines on Adolescents' Social Functioning

Abstract: Migraines dramatically affect adolescents' quality of life. One area of particular importance is the impact of migraines on adolescents' social functioning. Objective To understand the impact of migraines on adolescents' social functioning from multiple informants. Design Semi-structured interviews with adolescents who have migraines, their caregivers, and clinicians who treat adolescents who have migraines. Results Three major themes related to social functioning were identified from the adolescent inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Few studies have assessed the impact of migraine on the families of patients, their partners and children, and all report detrimental effects on QoL and social/leisure time . For adolescents, the impact of migraine on social functioning is particularly important in the family and the wider social context . A qualitative interview‐based study of adolescents with migraine, their caregivers, and the treating clinicians showed social functioning impairment of the adolescents because of the recurrent pain, and that this also had a negative impact on the family, parents, and siblings .…”
Section: Burden Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have assessed the impact of migraine on the families of patients, their partners and children, and all report detrimental effects on QoL and social/leisure time . For adolescents, the impact of migraine on social functioning is particularly important in the family and the wider social context . A qualitative interview‐based study of adolescents with migraine, their caregivers, and the treating clinicians showed social functioning impairment of the adolescents because of the recurrent pain, and that this also had a negative impact on the family, parents, and siblings .…”
Section: Burden Of Diseasementioning
confidence: 99%
“…For adolescents, the impact of migraine on social functioning is particularly important in the family and the wider social context . A qualitative interview‐based study of adolescents with migraine, their caregivers, and the treating clinicians showed social functioning impairment of the adolescents because of the recurrent pain, and that this also had a negative impact on the family, parents, and siblings . A longitudinal, U.S. internet‐based study investigated the impact of migraine on the family from the perspective of patients and their spouses .…”
Section: Burden Of Diseasementioning
confidence: 99%
“…Next, we applied the aforementioned criteria (C2-C5). Consequently, 20 studies (Bandell-Hoekstra et al, 2002;Caes, Fisher, Clinch, Tobias, & Eccleston, 2015;Carter et al, 2002;Castarlenas et al, 2015;Donovan et al, 2013;Eccleston, Wastell, Crombez, & Jordan, 2008;Forgeron et al, 2011;Forgeron & McGrath, 2008;Greco et al, 2007;Guite, Logan, Sherry, & Rose, 2007;Karwautz et al, 1999;Kashikar-Zuck et al, 2007;Konijnenberg et al, 2005;Langeveld et al, 1997;Larsson & Sund, 2007;Meldrum et al, 2009;Metsähonkala et al, 1998;Vannatta et al, 2008;van Tilburg et al, 2015) met inclusion criteria and were included in the review (Figure 1). The two articles excluded for not being primary sources (C1) were fully reviewed to scan their reference lists because one of them was an outstanding systematic review, and the other was a commentary related to the aims of our study.…”
Section: Resultsmentioning
confidence: 99%
“…Participants recruited were from 6 to 18 years old. Participants in 11 of the studies (Caes et al, 2005;Carter et al, 2002;Donovan et al, 2013;Forgeron et al, 2011;Greco et al, 2007;Kashikar-Zuck et al, 2007;Langeveld et al, 1997;Larsson & Sund, 2007) were between 12 and 18 years old. Six other studies included children under 10 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation